Предмет: Математика,
автор: dobroslav888
log2(x-1) = log4(x-1)
Ответы
Автор ответа:
0
Log₂(x-1) = log₄(x-1)
Т.к. log₄(x-1)=log₂²(x-1)=log₂(x-1)/2=0.5log₂(x-1),то получаем:
log₂(x-1) = log₄(x-1) = 0.5log₂(x-1) или log₂(x-1)- 0.5log₂(x-1)=
= 0.5log₂(x-1)=0, x-1=2⁰,x-1=1,x=2
Т.к. log₄(x-1)=log₂²(x-1)=log₂(x-1)/2=0.5log₂(x-1),то получаем:
log₂(x-1) = log₄(x-1) = 0.5log₂(x-1) или log₂(x-1)- 0.5log₂(x-1)=
= 0.5log₂(x-1)=0, x-1=2⁰,x-1=1,x=2
Автор ответа:
0
log(2, x-1) = log(4, x-1)
ОДЗ: x-1>0
log(2^2, (x-1)^2) = log(4, x-1)
log(4, (x-1)^2) = log(4. x-1)
Отсюда (x-1)^2=(x-1),
(x-1)(x-1-1)=0
То есть
1) x-1=0 => x=1. Корень не удовлетворяет ОДЗ: 1-1=0.
2) x-2=0 => x=2. Удовлетворяет ОДЗ.
Ответ: 2.
ОДЗ: x-1>0
log(2^2, (x-1)^2) = log(4, x-1)
log(4, (x-1)^2) = log(4. x-1)
Отсюда (x-1)^2=(x-1),
(x-1)(x-1-1)=0
То есть
1) x-1=0 => x=1. Корень не удовлетворяет ОДЗ: 1-1=0.
2) x-2=0 => x=2. Удовлетворяет ОДЗ.
Ответ: 2.
Похожие вопросы
Предмет: Информатика,
автор: livickaaalisa7
Предмет: Математика,
автор: kamillabogdanova0083
Предмет: Другие предметы,
автор: glebushkina84
Предмет: География,
автор: mynewtab221
Предмет: Биология,
автор: albinagugueva